Una visión cotidiana del derecho: pluralismo jurídico en el Mercado Revolución de Jacona - Navarro Rodríguez, Jesús (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
The empirical analysis from the social places shows how complex social relations are. In the mercado revolución of Jacona, the subjects reproduce social interactions, roles of characters acting on the daily life stage. They improvise from certain rules, some of them with common sense that are assume and impose depending on the role that they play on the mercado revolución: seller, dealer, employee, police, sweeper, plasero, customer and so on. In the market stage can not be unobserved the visual appeal, the public absorption to one of the ritual forms of consumption, buy and sell. This assignment highlights the existence or rather the coexistence of various organizations that organize the market space in different ways. The trader’s organization, and the organization of the city hall of Jacona. In the places arrangement, each organization creates a legal pluralism, their own forms of law. Each organization and their different types of law are relatively autonomous. This analysis focuses on the organization and forms of law for traders, even when they don’t lose sight of the interaction of this organization and their own law with the organization and the law form of the state in the mercado revolución.

El análisis empírico de los espacios sociales muestra la complejidad de las relaciones sociales. En el mercado revolución de Jacona se reproducen interacciones sociales entre distintos sujetos, roles de personajes que actúan en uno de los escenarios de la vida diaria, improvisan a partir de ciertas reglas, algunas de sentido común, que se asumen e imponen desde el papel en el cual se vive: comerciante, empleado de algún comerciante, placero, policía, barrendero, cliente, etcétera. En el escenario del mercado, no pasa desapercibido el atractivo visual, la absorción del público hacia una de las formas rituales del consumo, la compra y venta. En este trabajo se resalta la coexistencia de diversas organizaciones que ordenan el espacio social del mercado revolución, la organización de los comerciantes y la organización del Ayuntamiento de Jacona. En la ordenación del espacio, ambas organizaciones crean formas jurídicas propias, pero relativamente autónomas. El análisis se enfoca en la organización y la forma jurídica de los comerciantes y su interacción con la organización y la forma jurídica estatal en el mercado revolución.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2014-0114; Humanidades; Espacio social; Práctica social; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/554